THE EFFECT OF PERCEPTION OF BENEFITS, EASE OF USE, RISK AND TRUST IN CUSTOMERS’ INTEREST IN USING BNI MOBILE BANKING: (Study at Bank BNI 46 Tanjung Balai Branch Office) - Yasmin, Ade Aurora; Dirbawanto, Nana Dyki (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
In order to achieve its goal and objective, BNI Bank as one of the largest state-owned banks in the financial services industry relies heavily on its customers to run its service processes. As a result, BNI Bank must enhance the perception of benefits, usability, trust, and risk. These elements seem to have a direct impact on consumer interest. This study aims to determine and analyze the perception of benefits on customer interest in mobile banking, the ease of use of Mobile Banking, the risk to the interests of mobile banking customers, and the level of trust in the interests of BNI mobile banking customers at the Tanjung Balai branch office. This research utilizes quantitative methodologies. The population and sample for this study were established using non-probability testing and a quota sampling technique with a total of 100 participants. This research utilizes both primary and secondary sources. The data analysis approach involves the data validity test, classical assumption test, multiple linear regression analysis test, partial test, simultaneous test, and coefficient of determination test. According to the results of this investigation, the value of the independent variable has a major impact on customer interest (Y), whereas trust (X4) has only a minor influence on customer interest.